Hubungan Rasio Profitabilitasterhadap Harga Saham - Yuniarti, Yuniarti (Jurnal Ekonomi STIEP ( JES ), 2019)
To find out the relationship between profitability ratios to stock prices used inferential research. Profitabilityratios are proxied byreturn on asset as variable X1, net profit margin as variableX2, gross profit margin asvariableX3, andreturn on equityas variable X4. The stock price is proxied by closing price as the variable Y.Analysis techniques using multiple linear regression, analysis coefficient of determination and testing ofhypothesis both F-test and T-test. The results of the regression analysis show that the constant value is equalto-52244,543, the value of b1or ROA is -118,398, the value ofb2or NPM is -85,300, the value of b3or GPM is405,349,and the value of b4or ROE is 99,054. The result of the hypothesis test show that simultaneously thereis a relationship between the ratios to stock prices, with a significant level of 0,042. Partially the averagesignificant level of the ratio of ROA, NPM and ROE to the stock price is above 0.05, meaning nothing todo.While the GPM ratio of stock prices has a significant level below 0.05, which means there is aconnection.Based on the partial hypothesis test, it is also known that the GPM variable is the most dominantvariable affecting stock prices with a beta value of 0.532.